2018
DOI: 10.1016/j.jconrel.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of etoposide - silk wafers for neuroblastoma treatment

Abstract: High-risk neuroblastoma requires surgical resection and multi-drug chemotherapy. This study aimed to develop an extended release, implantable and degradable delivery system for etoposide, commonly used for neuroblastoma treatment. Different concentrations of silk, a biodegradable, non-toxic, non-immunogenic material were employed to prepare etoposide-loaded wafer formulations. Secondary structure of silk in the formulations was characterized using Fourier Transform Infrared (FTIR) spectroscopy and optimized ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“… 14 16 Multiple release studies with antibiotics, chemotherapeutic drugs, and antibodies demonstrated the ability of silk to sequester, stabilize, and to provide sustained release of therapeutic molecules ranging from small molecule to complex proteins using a diverse set of silk material delivery formats such as foam, films, gels, tubes, and particles. 17 22 Previously, we demonstrated the fabrication of high-aspect-ratio silk MNs and showed the release of large molecules and antibiotics with these systems. 23 Silk-based MNs arrays were used for the successful delivery of vaccines against human immunodeficiency virus (HIV), influenza, Clostridium difficile , and Shigella .…”
Section: Introductionmentioning
confidence: 99%
“… 14 16 Multiple release studies with antibiotics, chemotherapeutic drugs, and antibodies demonstrated the ability of silk to sequester, stabilize, and to provide sustained release of therapeutic molecules ranging from small molecule to complex proteins using a diverse set of silk material delivery formats such as foam, films, gels, tubes, and particles. 17 22 Previously, we demonstrated the fabrication of high-aspect-ratio silk MNs and showed the release of large molecules and antibiotics with these systems. 23 Silk-based MNs arrays were used for the successful delivery of vaccines against human immunodeficiency virus (HIV), influenza, Clostridium difficile , and Shigella .…”
Section: Introductionmentioning
confidence: 99%
“…This drug prevents re‐ligation of single‐stranded DNAs during DNA replication resulting in cell death. Etoposide may cause some off‐target side effects such as myelosuppression, acute hypotension, nephrotoxicity, and activation of secondary leukemia in high‐risk patients (National Center for Biotechnology Information, 2018; Yavuz et al, 2018). GD2 is expressed on neural crest‐originated and peripheral nerve cancerous cells and it would be a good strategy to target this molecule by antibodies to deliver the drugs more effectively to the target (Gholizadeh et al, 2018).…”
Section: Nanocarriers Used In Drug Deliverymentioning
confidence: 99%
“…Drug‐loaded silk filmsSilk is a material that is easily formulated for different applications in medical sciences such as films, hydrogels, microparticles, NPs, microneedles, or combination materials that are completely degradable in vivo. Its biocompatibility makes it a good choice for use in treatment strategies (Yavuz et al, 2018). Many types of research have been done to determine the effectiveness of using silk films in patients with NB who have just experienced a complete or incomplete resection surgery.…”
Section: Nanocarriers Used In Drug Deliverymentioning
confidence: 99%
“…Current research focuses on generating implantable systems that can overcome Gliadel ® limitations like extending this approach to more therapeutics and prolonging the drug release period. In this scenario, materials like biocompatible silk [80] and poly(lactic-co-glycolic acid) (PLGA) [81] represent optimal candidates to advance this kind of technology since they can be loaded with different therapeutics and their ultrastructure can be tuned to achieve the fine controlled release of different drugs [82].…”
Section: Bypassing the Bbbmentioning
confidence: 99%